A organização do conhecimento arquivístico a partir da Diplomática: Elementos históricos e conceituais de um método em revisão - Tognoli, Natália Bolfarini [UNESP] (My University, 2015)
Recently Archival Science has used its interdisciplinarity connections to face the challenges offered by new forms of records creation. This paper presents the methodological support given by diplomatics studies, demonstrating how the object of Archival Science determines the method chosen for its organization and representation, and describes the adaptation of methods to the complexity of the document creation systems.
The organization of archival knowledge from diplomatics: Historical and conceptual elements for a method in review
Keywords: Archival science; Diplomatics; Document production; Methodology; Theory